Bereavement, Level Stress and Coping Mechanism among Teacher Education Students of Samar State University: College Bereavement Study - Perlito Sabulaan Domingo; Archie G. Labine; Trixie Joyce V. Capoqauin (Intelektual Pustaka Media Utama, 2016)
Bereavement is a severe stressor that should be addressed properly. The study of Teacher education is very tight as it prepares soon to educator that will light the future of other young children. This study sought to determine the Level of Stress and Coping Mechanism on Bereavement among Teacher Education Students of Samar State University. It tested some assumption using the descriptive survey method on 76 identified students who experienced bereavement. It shows that respondent manifested highly emotional and physical stress rather than behavioral stress. It shows that social support is coping mechanism. The said study being the first bereavement research in the city could provide baseline information in the field of bereavement.